Transcriptome profiling at osmotic and ionic phases of salt stress response in bread wheat uncovers trait-specific candidate genes - Diana Duarte-Delgado; Said Dadshani; Heiko Schoof; Benedict C. Oyiga; Michael Schneider; Boby Mathew; Jens Léon; Agim Ballvora (BMC Plant Biology, 2020)
Abstract Background Bread wheat is one of the most important crops for the human diet, but the increasing soil salinization is causing yield reductions worldwide. Improving salt stress tolerance in wheat requires the elucidation of the mechanistic basis of plant response to this abiotic stress factor. Although several studies have been performed to analyze wheat adaptation to salt stress, there are still some gaps to fully understand the molecular mechanisms from initial signal perception to the onset of responsive tolerance pathways. The main objective of this study is to exploit the dynamic salt stress transcriptome in underlying QTL regions to uncover candidate genes controlling salt stress tolerance in bread wheat. The massive analysis of 3′-ends sequencing protocol was used to analyze leave samples at osmotic and ionic phases. Afterward, stress-responsive genes overlapping QTL for salt stress-related traits in two mapping populations were identified. Results Among the over-represented salt-responsive gene categories, the early up-regulation of calcium-binding and cell wall synthesis genes found in the tolerant genotype are presumably strategies to cope with the salt-related osmotic stress. On the other hand, the down-regulation of photosynthesis-related and calcium-binding genes, and the increased oxidative stress response in the susceptible genotype are linked with the greater photosynthesis inhibition at the osmotic phase. The specific up-regulation of some ABC transporters and Na+/Ca2+ exchangers in the tolerant genotype at the ionic stage indicates their involvement in mechanisms of sodium exclusion and homeostasis. Moreover, genes related to protein synthesis and breakdown were identified at both stress phases. Based on the linkage disequilibrium blocks, salt-responsive genes within QTL intervals were identified as potential components operating in pathways leading to salt stress tolerance. Furthermore, this study conferred evidence of novel regions with transcription in bread wheat. Conclusion The dynamic transcriptome analysis allowed the comparison of osmotic and ionic phases of the salt stress response and gave insights into key molecular mechanisms involved in the salt stress adaptation of contrasting bread wheat genotypes. The leveraging of the highly contiguous chromosome-level reference genome sequence assembly facilitated the QTL dissection by targeting novel candidate genes for salt tolerance.